Resurrection and Ascension (Joh 20:14-18) - A Johannine Theological Perspective of Jesus’ Appearance to Mary Magdalene - TOFANĂ, Stelian (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
In this article, I pointed out a few aspects from the episode of the meeting between the risen Jesus and Mary Magdalene on the morning of the Resurrection day (Joh 20:14-18). I have undertaken this analysis by taking into account the paschal theological Perspective of John the Evangelist. By doing this, I have tried to emphasize the identification between the Resurrection of Jesus and His "Ascension" that is equal with His Exaltation which Jesus speaks to Mary Magdalene about. This identification between the two seemingly distinct episodes with a single saving act, i.e. His Exaltation, constitutes a feature of John's Paschal Theology.